43rd AIAA Aerospace Sciences Meeting and Exhibit 2005
DOI: 10.2514/6.2005-1311
|View full text |Cite
|
Sign up to set email alerts
|

Highly Accurate Numerical Simulations of Pulsating One-Dimensional Detonations

Abstract: A novel, highly accurate numerical scheme based on shock-fitting coupled with high order spatial and temporal discretization is applied to a classical unsteady detonation problem to generate solutions with unprecedented accuracy. The one-dimensional reactive Euler equations for a calorically perfect mixture of ideal gases whose reaction is described by single-step irreversible Arrhenius kinetics are solved in a series of calculations in which the activation energy is varied. In contrast with nearly all known s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…In this paper, we describe and implement a new algorithm tailored to simulate a well established model problem: one-dimensional unsteady detonation; this study gives full details of recently reported results [1]. The new predictions are many orders of magnitude more precise than those previously published; this enhanced precision enables the prediction of remarkable new bifurcation phenomena.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this paper, we describe and implement a new algorithm tailored to simulate a well established model problem: one-dimensional unsteady detonation; this study gives full details of recently reported results [1]. The new predictions are many orders of magnitude more precise than those previously published; this enhanced precision enables the prediction of remarkable new bifurcation phenomena.…”
Section: Introductionmentioning
confidence: 91%
“…This scheme is a conservative flux difference method, which has been shown to be stable, and yields the proper viscosity-vanishing solution to Eqs. (1). The derivation of the difference operator LðuÞj x¼xi in Eq.…”
Section: Weno5mmentioning
confidence: 99%
“…Moreover, one can turn to studies from the shock fitting literature to find convergence rates consistent with the nominal order of the discretization method. For example, the recent study of Brooks and Powers 29 shows spectral convergence to machine accuracy on a coarse 65 × 33 grid for a blunt body re-entry problem, and the results of Henrick, et al 30 exhibit true fifth order accuracy which gives rise to predictions of detonation instabilities which agree remarkably well with those of linear stability theory.…”
Section: Discussionmentioning
confidence: 80%
“…Equations (30)(31)(32)(33) have full equivalents in Refs. 10-12, 14 and 16, albeit in slightly different notation.…”
Section: B Extended Rankine-hugoniot Conditionsmentioning
confidence: 99%